Endogenous entry in contests - John Morgan; Henrik Orzen; Martin Sefton (The University of Nottingham, Centre for Decision Research and Experimental Economics (CeDEx), 2008)
We report the results of laboratory experiments on rent-seeking contests with endogenous participation. Theory predicts that (a) contest entry and rent-seeking expenditures increase with the size of the prize; and (b) earnings are equalized between the contest and the outside option. While the directional predictions offered in (a) are supported in the data, the level predictions are not. Prediction (b) is not supported in the data: When the prize is large, contest participants earn more than the outside option. When the prize is small, contest participants earn less. Previous studies of gender and contest competition suggest that females should (a) not perform as well in the contest; and (b) enter at a lower rate. We find some support for (a) but not for (b). Women participate in the contest at the same rate as men.
Keywords: C9; D4; D72; 330; contests; competition; entry; experiments; Rent Seeking; Gewinn; Geschlecht; Test